1996
DOI: 10.1590/s0101-81751996000400015
|View full text |Cite
|
Sign up to set email alerts
|

Size of and damage on shoots of Passiflora suberosa (Passifloraceae) influence oviposition site selection of Heliconius erato phyllis (Fabricius) (Lepidoptera, Nymphalidae)

Abstract: ABSTRACT. Oviposition site selection of Heliconius erato phyllis (Fabricius, 1775) (Lepidoptera, Nymphalidae) was studied when size of and damage on shoots were variable in a natural population of Passijlora suberosa Linnaeus (passifloraceae), and through sequential and simultaneous choice experiments performed under insectary conditions. Females showed marked oviposition preference for undamaged and largest shoots of P. suberosa. Eggs were mostly laid on the terminal buds of intact shoots under natural condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…The fact that these caterpillars are cannibals in the wild could explain the oviposition behavior of this butterfly, which lays one egg in the apical portion of the host plant and goes on searching for another apical portion in the same or another host plant (Mugrabi-Oliveira and Moreira 1996), as well as the evolution of egg mimicry in some species of Passiflora (Gilbert 1982). The purpose in our experiments of using thick paper sheets and not Passiflora leaves was precisely to avoid letting the preference for a type of food influence the results.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that these caterpillars are cannibals in the wild could explain the oviposition behavior of this butterfly, which lays one egg in the apical portion of the host plant and goes on searching for another apical portion in the same or another host plant (Mugrabi-Oliveira and Moreira 1996), as well as the evolution of egg mimicry in some species of Passiflora (Gilbert 1982). The purpose in our experiments of using thick paper sheets and not Passiflora leaves was precisely to avoid letting the preference for a type of food influence the results.…”
Section: Resultsmentioning
confidence: 99%
“…Larvae fed shoots of P. misera result in larger adults, and body size is directly correlated to higher fecundity in this species (Rodrigues & Moreira 2002). According to Mugrabi-Oliveira & Moreira (1996a), other qualitative aspects of the shoot and host plant inspected by the female is the presence of an intact apical region, shoot size, leaf area and internode size. Fertilised plants possess advantages in such attributes, since shoot growth rate, leaf area and internode length of P. suberosa were higher in those cultivated with nitrogen addition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies carried out in our laboratory demonstrated that larvae prefer feeding on P. misera over P. suberosa, and that feeding preference can not be induced in the larval stage (S. M. Kerpel, UFRGS, unpublished data). H. erato females preferentially oviposit on intact, apical Passiflora shoots compared to damaged ones (Mugrabi-Oliveira & Moreira, 1996b). On a given intact Passiflora shoot, a newly hatched larva typically selects the youngest tissue for feeding, which allows it to achieve greater survivorship and development rate compared to those that feed on mature leaves, but not necessarily a larger pupal size (Rodrigues & Moreira, 1999).…”
Section: Introductionmentioning
confidence: 99%